ChemInform Abstract: Enantioselective Borane Reduction of Ketones Catalyzed by Tricyclic 1, 3, 2‐Oxazaborolidines. Issue 38 (September 2016) - Kaldun, Johannes; Krimalowski, Alexander; Breuning, Matthias
Abstract: Novel tricyclic oxazaborolidines are synthesized in seven steps from methyl Boc‐L‐pyroglutamate and utilized as catalyst in the asymmetric borane reduction of various ketones with excellent enantioselectivities.